DETERMINAN NILAI PERUSAHAAN DENGAN MEDIASI MARKETING EXPENSE (STUDY PADA PERUSAHAAN RETAIL DI BEI) - Hikmantara, Yusfi; Djaddang, Syahril (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
The purpose of this research is to examine and analyze the effect of profitability, leverage, tax avoidance as an independent variable on firm value as the dependent variable, with marketing expense as a intervening variable. This research was conducted at retail trading companies listed on the Indonesia Stock Exchange for the period 2016-2018. The population in this study amounted to 25 companies. The sample selection uses a purposive sampling technique, so that a total sample of 58 data is obtained. The result of this research shown that: (1) profitability positively significant affect marketing expense; (2) leverage negatively not significant affect marketing expense; (3) tax avoidance negatively significant affect marketing expense; (4) profitability positively significant affect firm value; (5) leverage negatively not significant affect firm value; (6) tax avoidance positively not significant affect firm value; (7) marketing expense negatively not significant affect firm value.